Assessing the impact of digitalization on the infrastructure construction industry's sustainable development : Infrakit Group Oy - Syrjälä, Jere (My University, 2022)
Sustainable development is becoming an increasingly more important topic across humanity whereas policymakers, financiers, and industries are required to set it to be increasingly higher in their priorities. The infrastructure construction industry and its stakeholders are among others increasing sustainable development constantly higher in the rank of priorities, but solutions for achieving the objectives have been in short supply. This study aims to answer the question: How is digitalization perceived to impact the infrastructure construction’s sustainable development? As digitalization as a growing trend has been estimated to be one of the most potential technologies enabling the pursuit of sustainable development, this study aims to assess its current impact on the sustainable development of the infrastructure construction industry. Identifying digitalization’s current impact and future opportunities could encourage technology developers and stakeholders of the industry to either foster the appliance of digitalization to achieve their sustainable development objectives or ignore the technology To assess the impact, this study conducted research through a method of survey research the perceptions of the stakeholders who have already applied digitalization solutions extensively in their operations. Additionally, this study explored the future opportunities of digitalization, which eventually was delivered by designing a data model for measuring CO2e emissions of projects. Eventually, this study discovered digitalization to have already a relevant impact on enabling sustainable development in the industry, especially by enhancing the management of projects and communication among stakeholders, and identified several development opportunities, which could enable the industry to achieve increased sustainability.

Kestävän kehityksen kasvattaessa merkitystään yhtenä ihmiskunnan tärkeimmistä tavoitteista, poliittisten päättäjien, rahoittajien ja yritysten on kasvavissa määrin asetettava se myös omissa tavoitteissaan etusijalle. Myös infrarakennusteollisuus ja sen sidosryhmät ovat nostamassa kestävää kehitystä jatkuvasti korkeammalle prioriteettilistallansa, mutta ratkaisujen löytäminen tavoitteiden saavuttamiseksi on ollut haasteellista. Työn tavoitteena on vastata tutkimuskysymykseen : Kuinka digitalisaation havaitaan vaikuttavan infrarakentamisen rakennusvaiheen kestävään kehitykseen? Digitalisaation on arvioitu omaavan paljon potentiaalia kestävän kehityksen edistämiseen, jonka vuoksi tutkimuksessa pyritään arvioimaan sen nykyistä vaikutusta infrarakentamisen kestävään kehitykseen. Digitalisaation nykyisten vaikutusten ja tulevien mahdollisuuksien tunnistaminen voi rohkaista teknologian kehittäjiä sekä alan sidosryhmiä edistämään digitalisaation käyttöä kestävän kehityksen tavoitteidensa saavuttamiseksi. Vaikutusten arvioimiseksi tutkimuksessa käytettiin kyselytutkimusmenetelmää tutkimaan niiden sidosryhmien näkemyksiä, jotka ovat jo laajasti soveltaneet toiminnassaan digitalisaatioratkaisuja. Lisäksi tutkimuksessa selvitettiin digitalisaation tulevaisuuden mahdollisuuksia, mikä johti projektien CO2e päästöjen mittaamista kehittävän tietomallin suunnitteluun. Tutkimuksessa havaittiin digitalisaatiolla olevan jo merkityksellinen vaikutus alan kestävän kehityksen mahdollistamiseen, erityisesti tehostamalla projektien hallintaa ja sidosryhmien keskinäistä viestintää, jonka lisäksi tunnistettiin useita teknologian kehitysmahdollisuuksia, joiden avulla toimiala voi saavuttaa kestävämpää kehitystä.
Keywords: sustainable development; digitalisation; construction industry; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Systems Analytics